Assessment of Interprofessional Education (IPE) in Community Settings: A Systematic Review - Asmara, Fatikhu Yatuni; Kristina, Tri Nur; Afifah, Diana Nur; Dewi, Dian Puspita (Department of Nursing, Faculty of Medicine, Diponegoro University, 2021)
Background: An assessment of methods and tools in interprofessional education (IPE) needs to be conducted to guarantee that the set learning objectives (LOs) or competencies are achieved, especially in community settings. This assessment is essential since in community settings, facilitators and students are not in the same frame, while direct observation is preferable in IPE. The implementation of methods and tools for assessment varies. Mostly, the assessment does not cover all competencies of IPE. Further identification of the way the assessment is conducted as well as the IPE competencies assessed is pivotal.Purpose: This study aimed to review the implementation of IPE in community settings, especially the assessment conducted on the methods and tools used along with the assessors involved and the competencies achieved.Methods: A systematic review was employed as a method in this study. Relevant articles from Science Direct, MEDLINE, CINAHL, and Scopus were screened based on the inclusion criteria: publication between 2010–2020, research and review articles, full-text articles, conducted in community settings, and involved assessment in acquiring the competencies. This review included 12 out of 1,273 screened articles. The articles were analyzed qualitatively by identifying the keywords, categories, and themes.Results: The results showed the assessment conducted and the competencies achieved in IPE. The assessment included methods and tools as well as the assessors involved. Most existing studies used students’ perceptions or reflections as the methods and involved less assessors such as supervisors or family members. Meanwhile, the assessment tools focused on certain competencies, such as roles and responsibilities, ethics and values, teamwork, and communication. However, no study assessed all competencies.Conclusion: The analysis resulted in two large topics, i.e., the assessment, which includes the assessment methods and tools as well as assessors involved, and the competencies achieved. It is recommended to conduct further studies to develop objective assessment methods, comprehensive assessment tools, and generic competencies or learning outcomes.